(untitled) (Sains Humanika, 2020)
Summative test is an evaluation process on students which is conducted comprehensively and administered at the end of a teaching and learning process. Evaluation is the benchmark for the success of a teaching and learning process which aims to determine the level of student achievement. The overall teaching objectives serve as the basis in the construction and administration of this summative test. Information from the summative tests conducted will be evaluated and interpreted about studentsâ€™ mastery level. The summative test conducted should also provide an overview to what extent the teaching objectives that have been set are achieved. The results of these summative test scores are then used in various evaluation and taken as Take Off Value (TOV) of students for the following year. Therefore, a study on a summative test instrument was conducted in identifying the difficulty index and item discrimination for the items contained in the summative test paper. A case study on this English Summative Test (Comprehension) was conducted towards 27 Year 5 students from the same class. The results of the study found that the items of summative test need to be modified. Besides, the students’ failure to get high marks and good grades in the summative test is due to the low item quality and low validity of the question. The results of this study have implications for subject teachers to improve the items in this summative test instrument in order to get accurate information on studentsâ€™ ability. The index of difficulty and discrimination of items provides information on studentsâ€™ strengths and weaknesses in a particular topic and also can provide an overview of the skills that need to be designed in the reinforcement and enrichment activities.